Liberdade individual e obediência às leis: crítica de Isaiah Berlin à teoria política de Jean-Jacques Rousseau - Almeida, Guilherme do Couto de (Universidade Federal de São Carlos, 2026)
In The Social Contract, Jean Jacques Rousseau sets out the political principles that govern the existence of the political body born of the social pact. By explicating the concepts of individual will, general will, and the common good, Rousseau maintains that the contracting individual receives his freedom from the pact, grounded in obedience to laws made by the people themselves. This freedom reflects popular sovereignty and the exercise of the general will as the guiding principle of the State and of civil society. The Genevan further qualifies this point by stressing that the associate preserves his individual freedom precisely by ordering his life through submission to the laws he himself has established. The present study aims to refute Isaiah Berlin’s critique of the individual freedom proposed by Jean Jacques Rousseau in The Social Contract. Berlin argues that Rousseau’s conception of freedom is illusory, claiming that the general will, when interpreted as an absolute, can lead to despotism and to the oppression of individual will. This study contends, however, that such criticism rests on a biased interpretation of Rousseau’s theory, especially insofar as it is grounded in a conception of freedom as the satisfaction of one’s own individual interests within the limits imposed by respect for the interests of others (negative liberty). The purpose is to address the core of the tension between individual freedom and collective authority through the lenses of Berlin and Rousseau—a theme that demands analytical precision and a deep grasp of its conceptual nuances. Berlin’s most forceful criticisms of Rousseau will be examined, especially as they concern the possibility that Rousseau’s ideas might conduce to tyranny or serve to justify totalitarian regimes. Accordingly, this dissertation proposes a critical analysis of Isaiah Berlin’s interpretation of Jean Jacques Rousseau’s political theory, specifically Rousseau’s conception of freedom and its implications for the organization of the State. The central hypothesis is that Berlin’s critique, although relevant within the context of twentieth century liberal thought, fails to grasp the complexity and the institutional safeguards present in Rousseau’s system—safeguards that prevent the degeneration of the general will into authoritarianism. More specifically, the research will examine how Rousseau articulates a political model in which genuine freedom is achieved not through the negation of individual will, but through its integration into the general will, expressed in laws collectively enacted. The method employed will consist in an exegesis of Rousseau’s primary texts - chiefly The Social Contract - and of Berlin’s writings, especially “Two Concepts of Liberty,” confronting them with the extensive secondary literature devoted to this controversy. The structure of the work, outlined below, is intended to deepen this analysis, culminating in a systematic response that reaffirms the continuing relevance of Rousseau’s political philosophy for understanding freedom and democratic legitimacy. Finally, the dissertation is grounded in a critical analysis of Rousseau’s works and of contemporary interpretations, seeking to clarify that individual freedom and the general will are not antagonistic, but complementary within the context of political life.
Liberté individuelle et obéissance aux lois : critique d’Isaiah Berlin de la théorie politique de Jean-Jacques Rousseau
Individual liberty and obedience to the laws: Isaiah Berlin’s critique of Jean-Jacques Rousseau’s political theory
Keywords: Rousseau; Isaiah Berlin; Liberdade negativa; Liberdade positiva; Liberdade individual; Vontade geral; Lei; Legislador; Contrato social; CIENCIAS SOCIAIS APLICADAS::DIREITO::TEORIA DO DIREITO::FILOSOFIA DO DIREITO; 10. Redução das Desigualdades